ENVIRONMENTAL SENSING SEBAGAI INFORMASI SUHU, KELEMBAPAN, DAN GAS BERBASIS IOT MENGGUNAKAN ESP 32 - Dwi Romadhona, Rizki; Faried Rahmat , Mohammad; Nugroho, Viery (Antivirus : Jurnal Ilmiah Teknik Informatika, 2024)
Current weather conditions in technological developments and climate change are a challenge to create safe and suitable conditions for carrying out activities both outdoors and indoors. The impact of climate change is that the research aims to create a monitoring and awareness system in work environment conditions and teaching and learning activities at the tertiary level. Objective: By utilizing technology that is currently mushrooming, such as IoT, to increase awareness of the importance of temperature, humidity and air quality in a room for teaching and learning activities and other activities in order to create a healthier work environment. Method: The method used is a wireless sensor network where sensors will read physical changes that occur such as methane and LPG gas anomalies, as well as changes in extreme temperature and humidity. Then the data that has been read is sent via ESP32 with an internet network connection to Blynk Cloud as universal monitoring between users and a personal dashboard which is used as a server to track history. Results: the results obtained with a sampling data collection period of approximately one hour, the condition of the room used for testing the DHT 22 sensor, and MQ2 indicated that there was no methane gas, or LPG contained in the room, indicated by ppm <300, as well as changes in temperature which were relatively stagnant did not occur in extreme changes where the average temperature obtained was 26.5˚C. The results from the humidity sensor showed that the room humidity was an average of 77.8%. These results can be interpreted as meaning that the room is still in a safe and comfortable condition for carrying out activities.